A novel process using human sera for the production of secretome and potentially clinical grade mesenchymal stem cell for regenerative therapy / Nazmul Haque - Nazmul , Haque (2017)
Introduction: Cell-based regenerative therapies offer tremendous hope to many individuals suffering from degenerative diseases. Mesenchymal stem cells (MSCs) are considered as an attractive source of stem cells for regenerative therapies. Like MSCs, cell culture supernatants and secretomes from peripheral blood mononuclear cells (PBMCs) have also shown regenerative potential. In vitro expansion of MSCs and culture of PBMCs are critical to obtain cells and secretomes with more regenerative potential. Usually, xenogeneic sera and purified recombinant proteins supplemented media are used for in vitro culture that may cause xeno-contamination and priming of cells eventually affect the regenerative outcomes. Objectives: Firstly, to compare the ability of pooled human serum (pHS) and foetal bovine serum (FBS), as supplement for the production of MSCs with more regenerative potential. Secondly, to assess the effect of autologous human serum (AuHS) and FBS in producing secretome from PBMCs. Methods: Stem cells from human extracted deciduous teeth (SHED) was used as a source of MSCs. SHED (n=3) was cultured with either pHS or FBS supplement to compare their suitability in maintaining the regenerative potential and immunomodulatory properties during in vitro expansion. The PBMCs (n=7) were cultured with either AuHS, FBS or without any serum supplement to measure viability and differentiation. Cytokines present in the secretome (n=6) were analysed. Ingenuity Pathway Analysis (IPA) were performed to predict the up/down-regulation of biological functions related to regeneration process. Results: SHED showed the characteristics of MSCs such as plastic adherence, expression of specific cell surface markers, and trilineage differentiation. Expanded SHED (n=3) showed significantly (p<0.05) higher proliferation in pHS medium compared to FBS medium. Significantly lower proportion of flattened cells was observed in pHS medium compared to FBS medium (FBS: 7%, pHS: 3%). Furthermore, migration of SHED in pHS medium was found more directional. Presence of selected 10 paracrine factors known for their proliferation and migration potential was detected in the human sera (n=6) that were used to produce pHS, none of which were detected in FBS. SHED expanded in pHS or FBS media were able to survive in the presence of complement and immune cells. IPA predicted results showed the suitability of pHS over FBS for the expansion of SHED to maintain their regenerative potential and immunomodulatory properties. Culture of PBMCs showed that AuHS supported viability of PBMCs until 96 hours of incubation. While with the FBS supplement, the viability of PBMCs was significantly reduced at 96 hours compared to those at 0 and 24 hours of incubation (p<0.05). A significantly higher content of EGF was detected in FBS secretome collected after 24 hours (p<0.05) compared to AuHS or basal medium secretome. While, AuHS secretome contained significantly higher amount of HGF after 24 (p<0.05) and 96 hours (p<0.01), and VEGF-A at 24 hours (p<0.05) compared to those in FBS secretome. SDF-1A was not detected in the FBS secretomes collected after either 24 or 96 hours. Conclusions: pHS has been shown to be better at supporting SHED to maintain its self-renewal capability, homogeneity and immunomodulatory properties. Besides, AuHS seems to favour cytokine composition of the secretomes with better regenerative potential.